Entrapment of Lactobacillus casei ATCC393 in the viscus matrix of Pistacia terebinthus resin for functional myzithra cheese manufacture. (March 2018) - Schoina, Vasiliki; Terpou, Antonia; Bosnea, Loulouda; Kanellaki, Maria; Nigam, Poonam S.
Abstract: Pissa Paphos, a natural mastic resin ( Pistacia terebinthus ) was evaluated as an encapsulating and matrix-forming material for the immobilisation of the probiotic bacterium Lactobacillus casei ATCC 393. The immobilized biocatalyst was added as an adjunct for the production of functional myzithra cheese. In total, four myzithra cheeses were manufactured: (a) Cheese with L. casei cells entrapped in P. terebinthus matrix (Pissa Paphos) (b) Cheese with free L. casei cells and P. terebinthus resin, (c) Cheese with free L. casei cells without the resin and (d) Traditional myzithra cheese. P. terebinthus resin provided antimicrobial properties by suppressing the growth of fungi/yeasts in myzithra cheeses during refrigerated storage. On the contrary, the presence of the resin did not affect the cell counts of the probiotic microorganism which maintained in high populations (above 9 log CFU g −1 ) during storage. Additionally, the viscus matrix of the resin seems to confer a protective effect on the entrapped L. casei cells since higher populations were observed over free cells. Moreover, all myzithra cheeses with incorporated resin were characterized by an exceptional mastic gum aroma and pleasant coherent texture which indicates the product's high commercialization potential. Highlights: Manufacture of a novel functional myzithra cheese with probiotic characteristics. Pistacia terebinthus viscus matrix as encapsulation support of probiotic lactobacilli . Significant reduction of fungi/yeasts in cheeses with incorporated Pistacia terebinthus resin. SPME GC/MS analysis indicates the upgraded terpene characteristics of cheeses with P. terebinthus resin. Terpene exceptional aroma and possible antimicrobial/antioxidant effects to cheese products.